2018
DOI: 10.1080/13607863.2018.1474447
|View full text |Cite
|
Sign up to set email alerts
|

Caregiving burden and psychological distress in Chinese spousal caregivers: gender difference in the moderating role of positive aspects of caregiving

Abstract: As these findings suggest that PAC is lower but more beneficial for Chinese wife caregivers than Chinese husband caregivers, helping professionals are recommended to use strengths-based interventions that target PAC when working with Chinese wife caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 45 publications
5
18
0
Order By: Relevance
“…In addition, having more parenting experience may be the reason for their lower parenting stress. Females are positively correlated with burden and parenting stress, which is consistent with most studies [ 25 27 ]. In traditional Chinese culture, females assume the role of caregivers and are responsible for family affairs [ 28 ].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, having more parenting experience may be the reason for their lower parenting stress. Females are positively correlated with burden and parenting stress, which is consistent with most studies [ 25 27 ]. In traditional Chinese culture, females assume the role of caregivers and are responsible for family affairs [ 28 ].…”
Section: Discussionsupporting
confidence: 91%
“…Carers had worse scores across the depression, anxiety, and stress scales when compared to the normative data (Henry and Crawford 2005). Our findings are consistent with previous research on carer distress which showed higher levels of depression, anxiety and stress were associated with higher burden (Wong et al 2018); we build upon these earlier findings by demonstrating that carers with high resilient coping have lower distress scores across all measures. This aligns with findings that resilience can improve wellbeing in other groups such as formal carers (Mealer et al 2012;).…”
Section: Discussionsupporting
confidence: 90%
“…The Depression Anxiety and Stress Scale (DASS-21) was used to assess psychological distress. The DASS-21 is a well-established measure of negative affect in adults and has been used in studies of family carers (Ervin et al 2015;Kumfor et al 2016;Wong et al 2018). It is a self-report measure that distinguishes between stress, anxiety and depressive states (Lovibond and Lovibond 1995).…”
Section: Psychological Distressmentioning
confidence: 99%
“…15 Hence, examining the relationship between psychological distress and caregiving burden is common in caregiver research as it provides an important perspective on the psychosocial burden of caregiving. 16,17 Despite NS being a chronic relapsing condition in most children and the heavy reliance on caregiver's input in the home management, few studies have examined the psychosocial well-being of caregivers of children with NS. 7,10,18 Indeed, the impact of NS on caregiver's health has received relatively little attention compared with other chronic childhood illnesses.…”
Section: Introductionmentioning
confidence: 99%